Finanzregulierung und internationale Wettbewerbsfähigkeit: Der Fall Deutsche Bundesliga - Oliver Budzinski; Anika Müller (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2013)
– [Financial Regulation and International Competitiveness: The Case of the German Bundesliga] The paper discusses the intensively discussed problem of financial crisis, overburdening debts and insolvencies in professional European football. The academic literature identifies several special characteristics of professional football leagues that allegedly lead to a systematic over-investment as well as features of a rat race. As a consequence, there are systemic market failures that warrant a regulative intervention by the competent national and European football associations. However, from an economics perspective, most of these alleged market failures turn out to be normal features of business competition. A closer inspection merely leaves two problems to be solved: (i) the widespread rescue of insolvent clubs (that are too prominent too fail) causing moral hazard issues and (ii) negative externalities on the league competition when an insolvent club would leave the market in the middle of the season. Even though these remaining issues may be viewed to justify regulations on the financial behavior of clubs by the league organizations, a note of caution needs to be issued: intervention may lead to over-regulation that distorts competition and, in particular, serves to cement the status quo competitiveness relations (i.e. preventing the incumbent top clubs from new emerging competitors). Furthermore, existing anticompetitive arrangements in football leagues contribute to the alleged market failure problems, so that more competition and not less competition may be the appropriate answer. A review of the pioneer financial regulations of the German Bundesliga allows for the conclusion that most of the German rules do not yet cross the line to over-regulation. However, the 50+1-rule, restricting newcomers from taking ownership of clubs (while protecting existing investments of the same type) clearly restricts competition and protects anticompetitive rents of incumbents. In the face of the upcoming UEFA-wide financial regulations, a first-mover effect may help German clubs to increase their international competitiveness.
Keywords: 330